Effect of daily use of fluoridated dentifrice and bleaching gels containing calcium, fluoride, or trimetaphosphate on enamel hardness: an in vitro study - Júnior, Ronaldo Antônio Tolentino Prette [UNESP] (2020)
Objective: This study evaluated the effects of calcium gluconate (CaGlu), sodium fluoride (NaF), sodium trimetaphosphate (TMP), and NaF/TMP added to a 35% hydrogen peroxide (HP) bleaching gel for the reduction in enamel demineralization in vitro, with and without the use of a fluoridated dentifrice. Design: Enamel blocks (n = 100) were obtained from bovine incisors (n = 200) after flattening and subjected to initial surface hardness (SH) analysis. The blocks were divided according to the bleaching gel (35% HP; 35% HP + 0.05% NaF; 35% HP + 0.25% TMP; 35% HP + 0.05% NaF + 0.25% TMP; 35% HP + 2% CaGlu) and were treated with ether non-fluoridated or fluoridated (1100 ppm) dentifrice. The bleaching gels were applied thrice (40 min/session) at the intervals of 7 days between each application. After 21 days, the final SH for the calculation of the percentage of SH loss (%SH) and cross-sectional hardness for the evaluation of the integrated hardness area (IH) were determined. Results: Bleaching containing HP + NaF + TMP presented lowest %SH (p < 0.001), regardless of the dentifrice used. HP + NaF + TMP bleaching gel led to lower subsurface enamel mineral loss (IH) compared to the other groups (p < 0.001), and these did not differ from each other (p > 0.05). Daily use of fluoride dentifrice led to higher IH values (p < 0.001), regardless of the bleaching gels. Conclusion: The addition of NaF/TMP to a 35% HP bleaching gel remarkably reduced the mineral loss compared to the cases of the other bleaching gels, regardless of dentifrice. Clinical relevance: The association of TMP/NaF can be used as a strategy for reducing mineral loss during the bleaching procedure, even without the daily use of fluoride dentifrice.